UTOPIA AND DESIRE - Martínez Herrera, Manuel (2022)
This article analyses the event of desire as a point of articulation between subjectivity and utopia, based on the relevant theoretical review. It reflects on the complex link between desire (whose origin is an impossible to satisfy) and the various utopias, their interrelationships, complementarities and tensions. It is concluded that utopian preferences have to do with subjective issues and demands, and not so much with argumentative aspects and principles of utopian systems.